واجبات الإعلاميين ومسؤوليتهم عن الإخلال بها في القانون العراقي - حمزة, وليد مرزة; الشمري, اشرف سلمان (Journal of Legal Sciences, 2019)
Practiced media work tasks within the scope of certain legal duties embody the whole rules of professional conduct that should be on the real media adhered to and act out because it or bring action would violate longer be positive for the legal liability of any kind. These legal obligations imposed on the media vary depending on the reference that media self-employed, there are legal obligations scheduled to journalists working for the state media institutions offset by other legal obligations imposed on those working in the private media institutions as well as the different nature as to each professional media in nature while others characterized the other character Public.Giving the media to exercise his legal rights, the media work freely under the principles of democracy and non-restricted except in accordance with the law must be matched deterrent system regulates the media in the event of failing to respect the legal mechanism drawn by the legislature when exercising his duties. So heading states at the present time about the organization and duties of the media and the development of a punitive regime governing the media work in all the establishment parties or institutions take this organization to achieve the required balance between freedom of information and expression and the deterrent device in front of this freedom because a deadly weapon his media multiple psychological, political, social and economic impacts that will build the general community or torn down, it is a double edged sword should take advantage of the positive aspects and good attention to the disadvantages .Hence begins the importance of finding a sober legal regime governing the duties of the media and the responsibility that may arise in Iraq whatever the media type legible or visible or audible and whether traditionally or electronically as the legal reality of Iraqi suffering mysterious and shortages for the provisions governing traditional media as well as the absence of the Governor's legal system Media mail is therefore needed to find a legislative treatment in Iraq would improve information work which can be achieved by adjusting the legal provisions in force and to propose new legal texts